PCSK9 Inhibitors and Ezetimibe Monotherapy in Patients Not Receiving Statins: A Meta-Analysis of Randomized Trials - Benhuri, Benjamin; Ueyama, Hiroki; Takagi, Hisato; Briasoulis, Alexandros; Kuno, Toshiki (Current Vascular Pharmacology, 2021)
Background: Statins are the mainstay of treatment for low-density lipoprotein cholesterol (LDL-C) lowering, however, some patients cannot tolerate statins because of adverse effects. Ezetimibe and proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) are alternative treatment options. The purpose of this meta-analysis was to compare LDL-C reduction with ezetimibe vs PCSK9i in patients not on statins. Methods: PubMed and EMBASE were searched until 14th March 2020 for randomized clinical trials (RCTs) assessing the efficacy of ezetimibe vs PCSK9i in patients not on statins. The primary outcome was a reduction in LDL-C levels. A subgroup analysis of statin intolerant patients was also performed. Results: We identified 8 RCTs that enrolled a total of 1602 patients comparing the two pharmacotherapies. PCSK9i lowered LDL-C levels significantly more than ezetimibe (mean difference (MD): -36.5; 95% confidence interval (CI) [-38.3, -34.7, p<0.00001, I2=4%]. In the statin intolerant subgroup, PCSK9i showed significantly greater reduction in LDL-C levels compared with ezetimibe (MD: -36.1; 95% CI [-39.2, -33.1, p<0.00001, I2=21%]. There were no significant differences in LDL-C reduction between different PCSK9i dosages (140 mg once every 2 weeks vs 420 mg once every 4 weeks) (MD: -1.87; 95% CI [-4.45, 0.71, p<0.16, I2=0]. Conclusion: Among patients who are statin intolerant or not receiving statins, PCSK9i use is associated with significantly lower LDL-C levels than after treatment with ezetimibe. PCSK9i might be useful in the prevention and treatment of atherosclerotic cardiovascular disease (ASCVD) in this subset of patients.
Keywords: statins